Stop antibiotic resistance – A roller coaster ride through “antibiotic stewardship,” “prescription auditing” and “AWaRe” assessment tool - Priyadharsini R. Palanisamy (Journal of Family Medicine and Primary Care)
The emergence of superbugs and highly resistant organisms like methicillin-resistant staphylococci, vancomycin-resistant enterococci, carbapenem-resistant enterobacteriaceae demands the monitoring of antibiotic prescription and usage in various domains. The impact of antibiotic resistance is huge that it increases mortality, morbidity, and economic costs. The issue has to be addressed at various levels and that is why regulatory bodies implement antibiotic stewardship programs. These programs give a list of guidelines like infection control, tracking antibiotic use, prescription auditing, and involvement of health professionals like pharmacists, nurses, etc., A comparison of the list of guidelines given by the Centre for Disease Control and Prevention and Indian Council of Medical Research gives an idea about the measures to be taken at various levels to reduce the burden of antibiotic resistance. Prescription auditing is one of the major components of antibiotic stewardship. The auditing can be done either prospectively or retrospectively using WHO core prescribing indicators and antibiotic-specific indicators. An AWaRe assessment tool was also used to evaluate antibiotic consumption in countries and hospitals. The antibiotics are classified into access, watch and reserve categories. The aim of implementing the AWaRe tool is to increase the rational use of access antibiotic and reduce the consumption of watch and reserve antibiotics. This review focuses on the importance of prescription auditing, AWaRe tool and antibiotic stewardship in decreasing the threat of antibiotic resistance.